A Wolff-Parkinson-White (WPW) Electrocardiographic Pattern in Asymptomatic Patient – State-of-the-Art-Review - Yadav, Vijay; Thapa, Sanjeev; Gajurel, Ratna Mani; Poudel, Chandra Mani; Manandhar, Bhawani; Sharma, Manju; Adhikari, Suman; Shrestha, Suraj (Journal of Cardiology and Cardiovascular Medicine, 2022)
A comprehensive approach to asymptomatic adults with Wolff-Parkinson-White (WPW) pattern discovered incidentally on routine electrocardiography (ECG) is debatable. The objective of this review article is to update the most recent evidence on the management of young patients with asymptomatic WPW patterns. A substantial proportion of adults with WPW patterns on ECG may remain asymptomatic but the lifetime risk for fatal arrhythmias still exists. The inherent properties of the accessory pathway determine the risk of sudden cardiac death. A low-risk pathway is considered when the pre-excitation is intermittent on ambulatory monitoring or when it disappears completely or abruptly during exercise testing. On the other hand, a high-risk pathway in EP study is suggested by the presence of the shortest pre-excited RR interval (SPERRI) during atrial fibrillation of ≤ 250 ms or accessory pathway effective refractory period (APERP) ≤ 240 ms. The cardiac evaluation may thus be considered in asymptomatic patients with WPW to determine the individual risk for future symptomatic arrhythmia. A shared-decision making must be performed before offering catheter ablation whose procedural success rate is high.